PENGEMBANGAN MODUL PEMBELAJARAN IPA BERBASIS MASALAH PADA MATERI HUKUM NEWTON DI MTs ISLAMIYAH PONTIANAK - Andriani, Reza; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study is a design to develop learning module with the considering of learner's appropriate ability and their respond to Sains Learning module based on Newton's Law problems The method of this study is Research and Development used Borg & Gall models with limited to the seventh stage. The subject of this study is Sains learning module based on the problems that will be done by VIII Grades of MTs Islamiyah Pontianak. The shape of this module consists of a cover, preface, table of contents, introduction, literature review and conclusions. The result of data indicate that this module is appropriate to used as the learning material with the persentage 82,22% (very high) and the appropriateness graphics 81,11% (very high). Learners respond on this module is 79,77% (high). The result of this study showes that Sains Learning Module based on Newton's Law Problem is appropriate as the learner's independent learning material. Keywords: Development, Problem Based Learning Module